Drug-related problems (DRPs) on antibiotic therapy in pediatric patients: a review - Titami, Arina; Mende, Juniarto; Nurfina Dian K. (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2022)
Drug-related problems (DRPs) is event that can interfere with the outcome of therapy. It can occur in various patient populations and ages. The DRPs in pediatric patients is found to be significantly frequent due to their vulnerable features. Many factors such as age, weight, body surface area should be considered during drug therapy in pediatric patients. The organs development continues for many years and the organs responsible for drug metabolism and elimination have not yet full capacity in pediatric patients. Antibiotics are often prescribed to pediatric patients. Several studies concerning DRPs on antibiotic therapy have been conducted in some countries. This review summarizes types, factors and impacts to the occurrence of DRPs on antibiotic therapy in pediatric patients.